The Effect Of Current Ratio (CR), Economic Value Added (EVA), And Debt To Equity Ratio (DER) On Stock Prices In The Banking Sector Listed On The Indonesia Stock Exchange For The 2017-2021 Period - Mardhiyah, Ainun; Karyatun, Subur; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to determine the effect of Current Ratio, Economic Value Added, and debt-to-equity ratio variables on Stock Prices in the banking sector listed on the Indonesia Stock Exchange for the 2017-2021 period. The population in this study is 45 companies from the banking sector listed on the Indonesia Stock Exchange 2017 – 2021 using the purposive sampling method, of which 22 companies match the criteria. The documentation uses a data collection method by conducting a panel data regression approach with a signification level of 0.05 through EViews 10 software. The results of this study show that the Current Ratio variable has no effect on Stock Price, Economic Value Added has a positive and significant effect on Stock Price, and Debt to Equity Ratio has a positive and significant effect on Stock Price.